Efficacy of three Tagetes species for the suppression of lepidopteran pests in bagless apple orchards - Shen, Jingwen; Wang, Haiyan; Zhao, Mingjie; Zhang, Ruifen; Zhang, Manman; Mao, Yunfei; Chen, Shaochao; Zhu, Cuixiang; Han, Tiantian; Shen, Xiang; Li, Shaoxuan (Frontiers in Agronomy, 2026)
BackgroundThe shift to bagless apple cultivation (i.e., fruit production without bagging) has increased the need for pest management during the summer and fall. The use of insect-repellent plants has become an effective biological control strategy in light of the increasing emphasis on reducing chemical pesticide applications and environmentally friendly integrated management strategies.MethodsIn this study, we evaluated the efficacy of three Tagetes species, marigold (Tagetes erecta L.), peacockweed (Tagetes patula L.), and Inca peacockweed (Tagetes minuta L.), intercropped in apple orchards for controlling major pests: the peach fruit moth (Carposina sasakii M.), fruit tree leaf roller (Spilonota lechriaspis M.), and apple leaf miner (Lithocolletis ringoniella M.). The relationship between pest suppression and volatile organic compound (VOC) profiles was further examined using gas chromatography–ion mobility spectrometry combined with principal component analysis.ResultsThe results indicated that all three Tagetes species reduced lepidopteran pest damage, with Inca peacockweed providing the most pronounced and stable control effect after four consecutive years of planting. Specifically, Inca peacockweed decreased the damage incidence to 1.8%, 1.5%, and 2.4% for peach fruit moth, apple leaf miner, and fruit tree leaf roller, respectively, within a 3 m radius, and the level of control declined with increasing distance from the Tagetes rows. VOC profiling revealed that ketones were the dominant compounds in marigold and peacockweed, whereas esters predominated in Inca peacockweed; VOC diversity was greater in flowers than in leaves.ConclusionOverall, this work provides a scientific foundation for optimizing ecological planting designs and offers new perspectives for the development of plant-based pest control strategies in sustainable apple production systems.